1962
DOI: 10.1093/bja/34.2.80
|View full text |Cite
|
Sign up to set email alerts
|

Oral Premedication in Children

Abstract: In view of the current interest in the subject of oral premedication in children it seemed desirable to stage a blind controlled clinical trial of drugs recently recommended by various authors. Pecazine has been recommended by Corssen and Allen (1958) and by Green (1959); trimeprazine by Cope and Glover (1959) and by Gunner and Fox (1960); and methylpentynol by Rendell (1954), Gusterson (1955) and by Kelsall (1957). In this trial the drugs were ordered to be administered 1 hour before operation in accordance w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1963
1963
1997
1997

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Furthermore, there produce sleep in the majority of younger patients is evidence that the frequency of crying and when used as a premedicant (18,21). There is probably struggling at induction is increased by the use of this synergism between the sedative properties of drug (31,38,39). While Phillips et al (32) and Layfield droperidol and diazepam, the latter having been et al (40) showed that the frequency of satisfactory noted to produce a greater sedative effect at anxiolytic sedation with trimeprazine could be improved by doses than other benzodiazepines (27).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, there produce sleep in the majority of younger patients is evidence that the frequency of crying and when used as a premedicant (18,21). There is probably struggling at induction is increased by the use of this synergism between the sedative properties of drug (31,38,39). While Phillips et al (32) and Layfield droperidol and diazepam, the latter having been et al (40) showed that the frequency of satisfactory noted to produce a greater sedative effect at anxiolytic sedation with trimeprazine could be improved by doses than other benzodiazepines (27).…”
Section: Resultsmentioning
confidence: 99%
“…Premedication with comparable anxiolysis on arrival at the anaesthetic larger doses of trimeprazine (4.0 mg·kg −1 ) has been room; however, anxiolysis was superior in the found to improve preoperative conditions by midazolam group at induction of anaesthesia. This increasing the proportion of children who were may be explained by the fact that butyrophenones, asleep or drowsy in the anaesthetic room (31,39); such as droperidol, are relatively ineffective against however, this was associated with a significantly acute situational anxiety such as that present during prolonged postoperative recovery time (21,39-41). induction of anaesthesia (28).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is conceivable that several other drugs with an absorption pattern similar to diazepam could be administered with an anticholinergic without effect on the rate of absorption, provided both drugs are administered orally at the same time. The satisfactory results of combining a sedative-hypnotic drug with an anticholinergic as oral premedication in children (Joseph and Vale, 1960;Doughty, 1962;Gordon and Turner, 1969) support this view. However, drug interactions in gastrointestinal absorption may be very complex, involving several mechanisms, so that the results of this study should be extended to other drugs with caution.…”
Section: Discussionmentioning
confidence: 95%